PENGARUH KEPEMIMPINAN KEUCHIK TERHADAP PEMBERDAYAAN EKONOMI MASYARAKAT GAMPONG DI KECAMATAN PEUSANGAN KABUPATEN BIREUEN - Subarni, Subarni; Yusuf, M.; Musrizal, Musrizal (Ekonomika Journal, 2022)
The research aims to analyze the influence of Keuchik leadership on the economic empowerment of gampong communities.  This is a case study in Peusangan District, Bireuen Regency in 2022. With a quantitative approach using questionnaire instruments and analysis using regression and correlation. The research results stated; (1) the success rate of keuchik leadership is not optimal at 79.81%. And the village government's efforts to empower the community's economy have only reached 75.37%, which is in line with expectations. (2) From the regression analysis, it is proven that there is a significant influence of keuchik leadership in empowering the community's economy. From the correlation analysis, it was obtained that the geuchiek leadership variable contributed 63% to the economic empowerment of the community in Peusangan sub-district, Bireuen Regency.